Development of a platform to interactively study cyber security malwares and threats - Le, Minh Viet (Nanyang Technological University, 2022)
Nowadays, cybersecurity has become a hot debate topic because of the rapid development of the Internet and increasing number of criminals in the Internet (cybercrime). In large organizations, it is difficult to keep the whole system secured; and the weakest link in the security chain is human. As a result, educating people about cybersecurity is crucial. Currently, in the market, there are numerous resources teaching about Cybersecurity. However, they are mostly theory-oriented and lack practical aspects. Unfortunately, practicality is one of the most important criterias in Cyber Security. Some companies also provide training in Cyber security, but usually require high-cost. As a result, there is a need for a platform to enhance the learning Cyber Security experience, yet, still at an affordable price. That platform should provide users not only theory material, but also hands-on coding activity. This project has been able to build out a platform that can be accessed as a web-application with the aforementioned functions. The project also implemented various Cyber Security topics which are demonstrated on the built platform. It is proved to be flexible enough to be able to discuss various topics or vulnerabilities in Cyber Security. The platform consists of multiple smaller independent components, so that it can be scaled-out to serve many users. The project is done through applying various Software Engineering knowledge and best practices on developing a web application. The main technology tools used to build it are: React.js, Flask (python), MongoDB, Docker, and Kubernetes.